Home, sweet home : Gupta’s real estate decision-b - Das, Prashant (London : Indian Institute of Management, Ahmedabad, 2024)
A salaried, upper-middle class couple in its 40’s is deciding whether to buy their home near their hometown, away from the city where they work. As they work in a distant city, the home they buy will be rented out. As such, homeownership appears to be an investment decision (versus consumption). They collect relevant market data and conduct financial analysis to assess the financial feasibility and prudence of homeownership. The raw data and set of information available offer conflicting signals related to homeownership. The only way out is to develop a detailed pro-forma spreadsheet. The case provides a systematic method to the classical real estate decision of households: should they buy a home or not? The case is a quasi Buy-versus-Rent analysis, and can serve to debate its pros and cons as well. The analysis is conducted (1) for owner-occupiers (to assess whether they should buy or rent the same unit); and (2) for investors who must decide whether home-buying is financially prudent.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Real estate business -- Case studies; Decision making -- Case studies